Analysis Racial Discrimination and Social Stratification in 12 Years a Slave - Sulastri Manurung; Mutia Ilma Sari (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This research aimed to describe racial discrimination found in 12 Years a Slave movie and to analyze social stratification reflected in 12 Years a Slave movie. 12 Years a Slave movie is tell about slavery in American at eighteen century which adapted from novel Twelve Years a Slave based on the real experience of author Solomon Northup who became a slave during 12 years. The research design was a qualitative with sociological approach to be analyzed. Then source of the data consisted of primary data and secondary data. Primary data source was 12 Years a Slave movie. Meanwhile, secondary data source derived from book, internet source and journal. The result of the research showed that racial discrimination against Niggers slave was found in form of less well treatment, restriction, insult, and distinction by white people. The researcher also found types of social stratification which included slavery, caste and class were caused by racial discrimination because there had a level position between white people and black people